Electrooptical Assay for Record of Antibiotic Action on Microbial Cells - O. I. Guliy; V. D. Bunin; O. V. Ignatov (Антибиотики и Химиотерапия)
Development of rapid and sensitive procedures for determination of microbial resistance to antibiotics is one of the most urgent trends in microbiology. The problem is shown to be solved by using electrooptical assay based on change of the electrophysical properties of suspended bacterial cells exposed to antibiotics with different mechanisms of action. Possible determination of the microbial cell susceptibility to antibiotics and their antibacterial activity is demonstrated. The results showed the procedure of electrooptical assay to be prospective in solving the problem of the microbiol cells antibiotic susceptibility in microbiology, medicine and veterinary.